[Au]-Catalyzed Cyclization of Propargyl-Tethered Ene-Amides: Substrate-Dependent Access to Tetrasubstituted Pyrroles, Aminophenols, and Dihydropyridines - Suraj; Swamy, K. C. Kumara (Journal of organic chemistry, 2024)
[Au]-catalyzed and substrate-dependent intramolecular cyclization of sulfonyl ene-amides with a pendant propargyl group afford tetrasubstituted pyrroles, o-aminophenols, or 1,6-dihydropyridine carbaldehydes. While the pyrroles and aminophenols are formed when the propargylic alkyne is terminal, dihydropyridines are formed when internal alkyne is present. Internal alkyne substrates with 2-thienyl and 3-thienyl groups give different types of dihydropyridines. The dihydropyridines so obtained can be readily converted to nicotinaldehydes with concomitant sulfonyl migration upon heating in xylene.